Cloud point preconcentration prior to capillary zone electrophoresis: Simultaneous determination of platinum and palladium at trace levels - Cerutti, Estela Soledad (2005)
The incorporation of a cloud point extraction (CPE) step prior to capillary electrophoresis (CE) for simultaneously determining platinum and palladium at sub-μg/L levels is presented and evaluated. The analytes were extracted as 2-(5-bromo-2-pyridylazo)-5-diethylaminophenol complexes, at pH 2.0, mediated by micelles of the nonionic surfactant polyethyleneglycolmono-p-nonylphenyl ether (PONPE 7.5). The separation-determination step was developed from 150 μL of the extracted surfactant-rich phase diluted with 50 μL of acetonitrile (ACN). An exhaustive study of the variables affecting the cloud point extraction with PONPE 7.5 and the CZE step was done. The type and composition of the background electrolytes (BGEs) were investigated with respect to separation selectivity, reproducibility, and stability. A BGE of 50 mM monobasic sodium phosphate containing 30% ACN, pH 4.53 was found to be optimal for the separation of metal chelates. Detection was performed at 576 nm. An enrichment factor of 250 was obtained for the preconcentration of 50 mL of sample solution. The detection limits for the preconcentration of 50 mL of sample were 0.04 μg/L for Pt and 0.08 μg/L for Pd. As an analytical demonstration, ultratrace concentrations of platinum and palladium were conveniently quantitated in spiked water and urine samples. © 2005 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.